Evaluation of spray drying microencapsulation for folic acid fortification of dried rice vermicelli (Khanom Jeen) - Phatthira Yingleardrattanakul; Ruchira Taprap; Praphan Pinsirodom (Food Chemistry Advances, 2024)
• Folic acid is essential for the human diet for growth and reproduction. • Microencapsulation is a popular processing application for food fortification. • Spraying microencapsulation is a good technique for protecting against the loss of folic acid and preserving it for a long time. • HPLC is a good and rapid technique for analysing folic acid in foods. • Khanom jeen is a common staple in Thai cuisine and has been enjoyed by people of all ages for a long time. This study evaluated spray drying (SD) microencapsulation of folic acid for physicochemical properties and its overall suitability for fortification of dried rice vermicelli. The SD microcapsules were formulated to achieve 30 µg of folic acid per 100 g of flour. The formula was homogenized into a 2% solid phase and made into a dry powder by the SD dryer, and the fortified dough was produced and dried in the final step. Fortified samples were analyzed for chemical and physical attributes, sensory evaluation, folic acid content, and stability in processing. The physical quality testing, water content, and the aw values were significantly different from controls ( P < 0.05). The acid content was not significantly different ( P > 0.05). Color difference, as assessed by a colorimeter, was significant ( P < 0.05). In the mixing, extrusion, and first and second washing steps, the coatings effectively prevented loss of folic acid during processing at 15, 12, 38, and 7% by wet weight, respectively. The folic acid content decreased significantly in the first 2 months of storage. In conclusion, for the fortification of flour this method was suitable and the SD microencapsulating technique can protect against folic acid loss during processing.
Keywords: Microencapsulation and Drying Processes; Food Quality and Safety Studies; Tea Polyphenols and Effects